2016
DOI: 10.3389/fmicb.2016.01429
|View full text |Cite
|
Sign up to set email alerts
|

Development of an in vitro Assay, Based on the BioFilm Ring Test®, for Rapid Profiling of Biofilm-Growing Bacteria

Abstract: Microbial biofilm represents a major virulence factor associated with chronic and recurrent infections. Pathogenic bacteria embedded in biofilms are highly resistant to environmental and chemical agents, including antibiotics and therefore difficult to eradicate. Thus, reliable tests to assess biofilm formation by bacterial strains as well as the impact of chemicals or antibiotics on biofilm formation represent desirable tools for a most effective therapeutic management and microbiological risk control. Curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 78 publications
2
58
0
Order By: Relevance
“…According to the intensity of the violet color of the stained biofilm, the biofilm-forming ability of different P. aeruginosa isolates was classified as strongly adherent, moderately adherent, weakly adherent, or nonadherent. In this work, P. aeruginosa strain PAO1 and strain PA14 were used as references for strong and weak adherent strains, respectively, where the biofilmproducing abilities for these standard strains were confirmed in previous reports [27][28][29].…”
Section: Qualitative Detection Of Biofilm With the Tube Methodssupporting
confidence: 65%
“…According to the intensity of the violet color of the stained biofilm, the biofilm-forming ability of different P. aeruginosa isolates was classified as strongly adherent, moderately adherent, weakly adherent, or nonadherent. In this work, P. aeruginosa strain PAO1 and strain PA14 were used as references for strong and weak adherent strains, respectively, where the biofilmproducing abilities for these standard strains were confirmed in previous reports [27][28][29].…”
Section: Qualitative Detection Of Biofilm With the Tube Methodssupporting
confidence: 65%
“…Biofilm production for each bacterial isolate was assessed by the clinical Biofilm Ring Test (cBRT) [27]. The results showed that S. aureus isolates were moderate (2/4 cases, including the MRSA) or high (2/4 cases) biofilm-producers.…”
Section: Quantification Of Biofilm Productionmentioning
confidence: 99%
“…Biofilm production was analyzed by the clinical BioFilm Ring Test (cBRT) (Biofilm Control, Saint Beauzire, France) as previously described [27]. S. aureus strains ATCC 25923 and Staphylococcus epidermidis ATCC 12228 were included in each plate as standard reference and internal control.…”
Section: Biofilm Productionmentioning
confidence: 99%
“…The capacity to form biofilm may be an advantage in Ralstonia spp. to face adverse conditions (Adley et al 2005;Anderson et al 1990;Di Domenico et al, 2016;Ryan et al 2011). Hence, it was hypothesized that the stressors aminoglycosides and arsenite could stimulate the capacity to produce biofilm (Fig.…”
Section: Effect Of Stressors In the Capacity Of Biofilm Formationmentioning
confidence: 99%